The nexus between corporate sustainability initiatives and audit opinion formulation: Elucidating the mediating function of financial reporting quality - Budiantara, Martinus; Nugroho, Mulyanto; Pandin, Maria Yovita R. (Edelweiss Applied Science and Technology, 2026)
This study examines the effect of sustainability practices on audit opinions by positioning financial reporting quality as a mediating mechanism. Specifically, the study investigates whether sustainability reporting, carbon emission disclosures, and sustainability performance influence audit opinions directly and indirectly through financial reporting quality among energy-sector companies listed on the Indonesia Stock Exchange for the period 2022–2024. A quantitative explanatory design was employed, utilizing secondary data obtained from annual reports, sustainability reports, and audited financial statements. The sample comprised 67 companies selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that sustainability reporting and sustainability performance significantly enhance financial reporting quality, whereas carbon-emission disclosures do not. Furthermore, sustainability reporting and carbon-emission disclosures exert significant positive effects on audit opinions, whereas sustainability performance exhibits no direct influence. Financial reporting quality has a significant positive effect on audit opinions and differentially mediates the relationship between sustainability practices and audit opinions. Specifically, the results indicate partial mediation for sustainability reporting, full mediation for sustainability performance, and no mediation for carbon-emission disclosures. This study contributes to the auditing and sustainability literature by demonstrating that distinct sustainability dimensions operate through varying audit-related mechanisms within an emerging-market context.